(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The wastewater from the automotive industries is one of the primary sources of oil and grease, heavy metals, cyanide, organic and inorganic pollutants that considerably adds to the pollution load of receiving water bodies and is vital for stream contamination. And also, nowadays automobile water treatment methods are highly energy demanding and expensive. In this study, the comparison of a floating and constructed wetland systems were carried out for finding, which is more effective in reducing the water quality parameters such as PH, BOD, COD, TSS and TDS. The plant selected for the floating system and constructed wetland were Eicchorniacrassipes and Eleusine indica respectively. Analysis of the result indicates that the characterized constructed wetland is an effective secondary treatment method as compared to the floating wetland system, as latter resulted in increase of BOD & COD due to the desiccation of water hyacinth. During the implementation of a constructed wetland with a retention time